مقارنة أداء خوارزميات جدولة المهام العشوائية في نظم الزمن الحقيقي - محمد حجازية; خلدون فاقي (Tishreen University, 2018)
تشكل نظم الزمن الحقيقي اليوم النواة الأساسية لمعظم التطبيقات المستخدمة في مجالات تقنية المعلومات والاتصالات، كما أن سرعة تطور مثل هذه النظم جذب اهتمام الباحثين من أجل تحقيق أداء أمثل والتخلص قدر الإمكان من المشاكل والمساوئ التي تعاني منها بغية تحسين أدائها بما يتناسب مع حجم المهام الموكلة إليها. توجد العديد من التحديات الأساسية التي تواجه نظم الزمن الحقيقي والتي تتجسد بالدرجة الأولى في مشكلة جدولة تنفيذ المهام على نوى المعالج في هيكلية المعالجات متعددة النوى حيث تم اقتراح العديد من الطرق منها ما اعتمد الطريقة العامة والتي تكون فيها أي مهمة قابلة للتنفيذ على أية نواة، أو الطريقة المجزأة التي تعتمد على تخصيص نواة معينة لكل مجموعة محددة من المهام، وهناك أيضاً الطريقة شبه المجزأة وهي عبارة عن هجين من الطريقتين السابقتين حيث يتم تخصيص مجموعة من المهام لكي تنفذ على نواة معينة في حين يسمح لمهام أخرى بالتنفيذ على أية نواة من نوى المعالج. تم في هذا البحث مقارنة أداء خوارزميات جدولة المهام العشوائية على منصة متعددة النوىبهدف تحديد الخوارزمية الأفضل من ناحية مجموعة من البارامترات المعتمدة من قبل الباحثين في هذا المجال والتي بدورها تعطينا تفاصيل دقيقة حول جودة مثل هذه الخوارزميات عند تطبيقها على مجموعة من المهام العشوائية المولدة وفق التوزع الاحتمالي اللوغاريتمي الموحد. تمت عملية المحاكاة على البرنامج simso والذي أثبت موثوقية أداء عالية بشهادة العديد من الباحثين في هذا المجال فضلاً عن كونه يقدم إمكانية توليد المهام وفق توزعات احتمالية معينة، ويحاكي تفاصيل دقيقة متعلقة بخصائص المهام العشوائية. Nowadays, Real-time systems are considered as the core of most applications that used in Telecommunication and information technology areas. The rapid development of such systems has attracted researchers' attention to optimize performance and eliminate problems and disadvantagesas possible in order to improve their performance in proportion to the volume of tasks assigned to them. There are many challenges facing real-time systems, mainly the problem of task scheduling on processor cores in the multi-core processor architecture. Several schemes have been proposed, including the global scheme, where any task can be executed on any core ,The partitionedscheme which depends on the allocation of a specific core for each set of tasks. There is also the semi-partitionedscheme, which is a hybrid of the two previous schemes, where a set of tasks is assigned to execute on a specific core while other tasks are allowed to be executed on any core of processor. In this paper, we compare the performance of sporadic tasks scheduler algorithms on a multi-core platform in order to determine the best algorithm in terms of a set of parameters adopted by researchers in this field, which in turn gives us accurate details about the quality of such algorithms when applied to a set of sporadic tasks generated according to  uniformed Logarithmic probability distribution. The simulation is done using Simso simulator, which proved the reliability of high performance by the testimony of many researchers in this field, as it provides the possibility of generating tasks according to specific probability distributions, and simulates accurate details related to the characteristics of random tasks